PENGARUH DESTINATION ATTRIBUTES DAN MEMORABLE TOURISM EXPERIENCE TERHADAP REVISIT INTENTION PADA GENERASI Z - Anisa Apriliani; Johannes; Ihsan, Moh (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to explain the influence of destination attributes and memorable tourism experience on revisit intention. The research employs a quantitative approach with data collected through an online questionnaire distributed via Google Form. The population is Generation Z, with samples determined using the purposive sampling technique. A total of 150 respondents who are students of Universitas Maritim Raja Ali Haji (UMRAH) were selected because they had visited Lagoi Bay at least once. The results show that most respondents experienced a clean beach atmosphere, comfortable facilities, and beautiful scenery that created a memorable travel experience. The findings indicate that destination attributes and memorable tourism experience have a positive influence on revisit intention. In other words, the better the destination’s attributes and the more memorable the tourist experience, the greater the visitors’ desire to return to Lagoi Bay.